Digital Marketing Promotion Strategy Bank Central Asia Tbk (BCA) - Napitupulu, Imelda Solagracia; Gunarto, Muji; Helmi, Sulaiman (Jurnal Ekonomi dan Bisnis Digital, 2024)
This research aims to analyze the digital marketing promotion strategy carried out by BCA Bank in increasing brand awareness and customer engagement. Using a qualitative descriptive approach, this study analyzes the use of various digital platforms such as social media, official websites, and mobile banking applications to deliver marketing messages. The results show that Bank BCA successfully utilizes an omnichannel strategy that integrates various digital platforms to provide a consistent and engaging experience for customers. The “Sharing Stories with BCA” campaign successfully increased user interaction and brand awareness. However, challenges included differences in preferences between customer segments and changes in social media algorithms that affected content visibility. This research suggests that Bank BCA should improve content personalization by leveraging artificial intelligence (AI) technology and customer preference analysis to create more relevant and effective campaigns.